Effects of mismatch parameters on the punch load during deep drawing - Wu, J.; Ma, Z.; Zhou, Y.; Lu, Chunsheng (American Scientific Publishers, 2013)
During deep drawing of a coated metal sheet, mismatch of mechanical parameters between coating and substratehas a significant effect on the formability. In this paper, theoretical analysis, dimensional analysis andfinite element simulation are used to study the influence of mismatch parameters on the punch load. It is shownthat there is a quantitative relationship between the maximum punch load, the elastic mismatch parameter andthe thickness ratio, which can guide the material selection of a coated metal sheet.